2018
DOI: 10.3390/rel9060189
|View full text |Cite
|
Sign up to set email alerts
|

God and Guns: Examining Religious Influences on Gun Control Attitudes in the United States

Abstract: Mass shootings in the United States have generated significant media coverage and public concern, invigorating debates over gun control. Media coverage and academic research on gun control attitudes and reactions to mass shootings have paid little attention to the role of religion. Recent research sheds light on the complex relationship between religion and guns, including higher rates of gun ownership and stronger opposition to gun control among white evangelical Protestants. Using nationally representative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Due to this mixed support, an array of proposed gun control measures and policies have faced backlash amid American constituents (see Giffords Law Center for a review of state-specific measures). Generally, though, this work has found that men (Ellison, 1991 ; Kauder, 1993 ; Livingston & Lee, 1992 ; Marciniak & Loftin, 1991 ; Merino, 2018 ; O’Brien et al, 2013 ; Pederson et al, 2015 ; Tyler & Lavrakas, 1983 ), whites (Filindra & Kaplan, 2017 ; McClain, 1983 ; Merino, 2018 ; Secret & Johnson, 1989 ), those who are politically conservative (Filindra & Kaplan, 2017 ; Merino, 2018 ), those who live in rural communities (Brennan et al, 1993 ; Parker et al, 2017 ) and gun owners (Filindra & Kaplan, 2017 ; Merino, 2018 ) are less supportive of more-restrictive forms of gun control than those in reference groups. Additionally, there is evidence suggesting that those who have greater exposure to, and familiarity with firearms (Ellison, 1991 ; Hill et al, 1985 ; Kruis et al, 2020 ; Rosen, 2000 ; Tyler & Lavrakas, 1983 ) favor more-permissive forms of gun control.…”
Section: Literature Reviewmentioning
confidence: 89%
See 2 more Smart Citations
“…Due to this mixed support, an array of proposed gun control measures and policies have faced backlash amid American constituents (see Giffords Law Center for a review of state-specific measures). Generally, though, this work has found that men (Ellison, 1991 ; Kauder, 1993 ; Livingston & Lee, 1992 ; Marciniak & Loftin, 1991 ; Merino, 2018 ; O’Brien et al, 2013 ; Pederson et al, 2015 ; Tyler & Lavrakas, 1983 ), whites (Filindra & Kaplan, 2017 ; McClain, 1983 ; Merino, 2018 ; Secret & Johnson, 1989 ), those who are politically conservative (Filindra & Kaplan, 2017 ; Merino, 2018 ), those who live in rural communities (Brennan et al, 1993 ; Parker et al, 2017 ) and gun owners (Filindra & Kaplan, 2017 ; Merino, 2018 ) are less supportive of more-restrictive forms of gun control than those in reference groups. Additionally, there is evidence suggesting that those who have greater exposure to, and familiarity with firearms (Ellison, 1991 ; Hill et al, 1985 ; Kruis et al, 2020 ; Rosen, 2000 ; Tyler & Lavrakas, 1983 ) favor more-permissive forms of gun control.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Other researchers have found that men, generally, are less supportive of more-restrictive forms of gun control (see Ellison, 1991 ; Merino, 2018 ; O’Brien et al, 2013 ; Pederson et al, 2015 ; Tyler & Lavrakas, 1983 ). Some scholars have suggested that guns and pro-gun attitudes serve as a way for men to demonstrate masculinity and to bond with other men.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Those that have explored this question have found that Protestants are not only more likely to own guns, but they are also less likely to support gun control. Merino (2018) finds that white evangelical Protestants are more inclined to address gun violence with policy interventions, such as expanded concealed carry laws, better mental health screenings, and a greater emphasis on God in public schools and society. A distinctive form of Christian nationalism––i.e., the belief that America was founded as a Christian nation and enjoys a special covenantal relationship with God––is associated with decreased support for gun control (Whitehead, Schnabel, and Perry 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“… 22. In earlier analyses, we included control variables known to influence views on gun control, including gender, race (i.e., white or non-white), religion (i.e., Protestant or other), income, and gun ownership (e.g., Mencken & Froese, 2019; Merino, 2018). Each of these variables fails to reach statistical significance in each of the nine models presented in this paper.…”
mentioning
confidence: 99%